2016
DOI: 10.12660/rbfin.v14n2.2016.57958
|View full text |Cite
|
Sign up to set email alerts
|

Persistência de Desempenho em Fundos de Ações no Brasil

Abstract: This paper aims to investigate the existence of persistence in superior performance in Brazilian stock market funds from 2001 to 2014. In order to do so, we used a sample free of survivorship bias and four different market models to characterize the expected return and risk relationship. In all models we were not able to find evidence consistent with superior performance, indicating performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
0
6
0
5
Order By: Relevance
“…Entretanto, há forte relação entre desempenho passado e desempenho futuro no longo prazo (Andaku & Pinto, 2003). Esse desempenho e sua persistência ao logo do tempo sofrem influências das características específicas dos fundos (Basso & Funari, 2017;Ceretta & Costa, 2001;Chen, Hong, Huang, & Kubik, 2004;Matos & Rocha, 2009;Melo & Macedo, 2013;Milani & Ceretta, 2013;Nerasti & Lucinda, 2016;Pollet & Wilson, 2008;Tran-Dieu, 2015).…”
Section: Estudos Da Performance De Ativos De Investimentounclassified
See 2 more Smart Citations
“…Entretanto, há forte relação entre desempenho passado e desempenho futuro no longo prazo (Andaku & Pinto, 2003). Esse desempenho e sua persistência ao logo do tempo sofrem influências das características específicas dos fundos (Basso & Funari, 2017;Ceretta & Costa, 2001;Chen, Hong, Huang, & Kubik, 2004;Matos & Rocha, 2009;Melo & Macedo, 2013;Milani & Ceretta, 2013;Nerasti & Lucinda, 2016;Pollet & Wilson, 2008;Tran-Dieu, 2015).…”
Section: Estudos Da Performance De Ativos De Investimentounclassified
“…Os métodos paramétricos consistem em modelos estatísticos que se prestam a mensurar a sensibilidade (parâmetros) dos retornos de ativos financeiros sujeitos a determinados construtos. Já os modelos não paramétricos buscam estabelecer relações ótimas entre as variáveis em análise, por meio da ponderação dessas variáveis e da observação dos impactos nos resultados sem pressupostos de distribuição ou parâmetros preestabelecidos (Basso & Funari, 2017;Fama & French, 2015;Nerasti & Lucinda, 2016).…”
Section: Estudos Da Performance De Ativos De Investimentounclassified
See 1 more Smart Citation
“…Os estudos nacionais e internacionais têm apontado preferência na utilização dos modelos de Fama e French (1993) e de Carhart (1997) para a mensuração do desempenho de fundos de investimentos (Carhart, 1997;Chen et al, 2004;Gil-Bazo & Ruiz-Verdú, 2009;Castro & Minardi, 2009;Nerasti & Lucinda, 2016;Paz, Iquiapaza & Bressan, 2007).…”
Section: Taxa De Administração E O Desempenho Da Indústria De Fundos unclassified
“…Jordão and Moura (2011) analyzed an extensive sample from Carhart (1997) model for stock-picking ability and from Treynor and Mazuy (1966) for market-timing and found that less than 5% of the funds presented positive and significant results for such skills. Nerasti and Lucinda (2016) investigated the persistence in the performance of Brazilian stock funds with four models: traditional CAPM, the three-factor model proposed by Fama and French (1993), Carhart's four-factor model (1997), and an additional model, adding the risk factor associated with asset liquidity. They did not find persistence in the superior performance of Brazilian managers.…”
Section: Introductionmentioning
confidence: 99%